1997
DOI: 10.3109/01902149709039235
|View full text |Cite
|
Sign up to set email alerts
|

Oleic Acid Reduces Oxidant Stress in Cultured Pulmonary Artery Endothelial Cells

Abstract: Altering the fatty acid composition of cultured porcine pulmonary artery endothelial cells (PAEC) modulates their susceptibility to oxidant stress. This study demonstrates that supplementing PAEC with oleic acid (18:1 omega 9), but not gamma-linolenic acid (18:3 omega 6), provided dose-dependent protection from hydrogen peroxide (H2O2)-induced cytotoxicity. It was hypothesized that 18:1 reduced PAEC susceptibility to oxidant stress by altering H2O2 metabolism. To test this hypothesis, confluent PAEC monolayers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 30 publications
2
3
0
1
Order By: Relevance
“…Studies have suggested that saturated and unsaturated fatty acids have different effects on toxicity. For example, there has been evidence indicating that dietary oleic acid can protect endothelial cells against hydrogen peroxide-induced oxidative stress and reduce the susceptibility of LDLs to oxidative modifications (23)(24)(25). Similarly, we found that oleic acid does not induce the same level of cytotoxicity as palmitic acid in HepG2 cells at similar concentrations (12) and the addition of oleic acid reduces the cytotoxicity induced by palmitate (26).…”
Section: Introductionsupporting
confidence: 63%
“…Studies have suggested that saturated and unsaturated fatty acids have different effects on toxicity. For example, there has been evidence indicating that dietary oleic acid can protect endothelial cells against hydrogen peroxide-induced oxidative stress and reduce the susceptibility of LDLs to oxidative modifications (23)(24)(25). Similarly, we found that oleic acid does not induce the same level of cytotoxicity as palmitic acid in HepG2 cells at similar concentrations (12) and the addition of oleic acid reduces the cytotoxicity induced by palmitate (26).…”
Section: Introductionsupporting
confidence: 63%
“…Indeed, decreased vascular inflammation and oxidative stress may be the mechanism by which the oil mixture treatment attenuates endothelial dysfunction in aged rats, as it significantly reduced the arterial expression of pro-inflammatory enzymes like COX-2 and prooxidant enzymes like NOX-4. Similarly, other authors have reported that both omega-3 and MUFA fatty acids supplementation exerts antioxidant and anti-inflammatory effects in arterial cells or tissue [ 79 , 83 ].…”
Section: Discussionmentioning
confidence: 70%
“…The consequence was an increase in resistance to derangements caused by oxidized LDL and a reduction in oxidant-mediated dysfunction [159,161]. Massaro et al [162] showed that the incubation of oleate with cytokine-stimulated endothelial cells prevents the depletion of glutathione (GSH) and partially prevents stimuli-induced increase of intracellular ROS.…”
Section: Effects Of Oleic Acidmentioning
confidence: 98%
“…Therefore, an alteration of H 2 O 2 metabolism in vascular cells may contribute to the ability of fatty acids to modulate cellular oxidant susceptibility [159].…”
Section: Effects Of Oleic Acidmentioning
confidence: 99%